БИОГРАФИЧЕСКИЙ ХРОНОТОП В НОВЕЛЛЕ ЮРИЯ НАГИБИНА «ОТ ПИСЬМА ДО ПИСЬМА» - Рахманова, М.У.; Воронцова, Н.В. (SCIENCE and SOCIETY, 2024)
This article highlights the main points of the chronotopic organization of Yuri Nagibin’s novella «From Letter to Letter» and their description.